SENTILING JAGUNG (SENJA) SEBAGAI INOVASI KUE TRADISIONAL - Endang Mulyatiningsih, Adilah Motik Az-Zahra (Prosiding Pendidikan Teknik Boga Busana, 2020)
Corn (Zea mays L.) is one of the most important world food crops, in addition to wheat and rice. As the main carbohydrate source in Central and South America, corn is also an alternative source of food in the United states, besides being a source of carbohydrates, corn has been genetic engineering is also now being grown as a producer oh pharmaceutical ingredients. In terms of nutrition of corn if calculated from 100 grams of material containing carbohydrates 19 grams, 3.2 grams of sugar, 2.7 grams fiber, 90 kcal calories, 32 grams of protein, 1.2 grams of fat, vitaminA is equivalent to 10 grams of 1% folate (Vit.B9) 4.6 grams 12%, iron 0.5 mg 4%, magnesium 37 mg 10%, potassium 270 mg 6%, water 24 grams. High nutritional value and relatively cheap prices make corn as a food ingredient to meet the needs of community nutrition. This provides an opportunity for the community to increase the utilization of corn as a functional food material such as making Sentiling Jagung (Senja). This development aims to find out the formula, technique, and presentation, which is suitable for Indonesia cake making, namely Sentiling Jagung. Research uses the stage of Research and Development or often called R & D. the results of untrained panelists at the exhibition produced a mean score from the aspects or colour 3.8; flavour 3.6; texture 3.8; taste 3.7; and overall 3.8; this shows that all aspects have values greater than 3 and close to 4, which means consumers receive and like the products of Sentiling Jagung. Keywords: Corn, Sentiling Jagung, Panelist Test.